Effects of temperature and relative humidity on the partitioning of atmospheric oxidized mercury at a high-altitude mountain background site in Taiwan. (15th September 2021) - Nguyen, Ly Sy Phu; Sheu, Guey-Rong; Chang, Shuenn-Chin; Lin, Neng-Huei
Abstract: Gas-particle partitioning of oxidized mercury (Hg) plays an important role in governing the speciation, transport and deposition of atmospheric Hg. Although studies on gas-particle partitioning of oxidized Hg have been conducted at some urban sites, comparable studies at remote mountain sites are still limited. This study analyzes multi-year (2014–2016) data of speciated atmospheric Hg concentrations from Lulin Atmospheric Background Station (LABS, 2862 m above sea level), Taiwan, to explore the factors that influence the gas-particle partitioning of atmospheric oxidized Hg. Mean concentrations (±S.D.) of gaseous elemental mercury (GEM), gaseous oxidized mercury (GOM), and particulate-bound mercury (PBM) were 1.54 ± 0.34 ng m −3, 14.5 ± 26.5 pg m −3, and 5.0 ± 12.0 pg m −3, respectively. In addition, our results indicated that the partitioning of Hg(II) toward particles was favored in the upper free troposphere and/or lower stratosphere. Both temperature (T) and relative humidity (RH) were found to strongly affect the gas-particle partitioning of oxidized Hg. Significant negative correlations between the partitioning coefficient ( K p ) and T were obtained for all seasons, but peaked in summer. When RH<30%, K p decreased with increasing RH. However, K p and RH were positively correlated when RH>30%. Two empirical K p -T and K p -T-RH regression equations: log(1/ K p ) = 15.0 – 3887.6(1/T) and log(1/ K p ) = 17.92 – 4390.0(1/T) – 0.016RH were developed for free tropospheric air downwind of continental East Asia, which could be implemented in a chemical transport model to improve our understanding of the Hg biogeochemical cycle. Graphical abstract: Image 1 Highlights: Gas-particle partitioning of Hg(II) was characterized at a mountain site in East Asia. Partitioning coefficient ( K p ) correlated with temperature negatively. K p increased with increasing relative humidity (RH) when RH>30%. However, K p decreased with increasing RH when RH<30%. Partitioning of Hg(II) toward particles was favored in the upper free troposphere.